Multidisciplinary engagement for fencing research informs efficacy and rancher-to-researcher knowledge exchange - Hyde, Matthew; Breck, Stewart W.; Few, Alex; Beaver, Jared; Schrecengost, Joshua; Stone, Jim; Krebs, Cameron; Talmo, Russell; Eneas, Kari; Nickerson, Rae; Kunkel, Kyran E.; Young, Julie K. (Frontiers in Conservation Science, 2022)
Across much of the Western United States, recovery of large carnivore populations is creating new challenges for livestock producers. Reducing the risks of sharing the landscape with recovering wildlife populations is critical to private working lands, which play an vital role in securing future energy, water, food, and fiber for an ever-expanding human population. Fencing is an important mitigation practice that many ranchers, land managers, and conservationists implement to reduce carnivore-livestock conflict. While fencing strategies have been reviewed in the literature, research seldom incorporates knowledge from the people who utilize fencing the most (i.e., livestock producers). Incorporating producers and practitioners early in the process of producing scientific knowledge is proving to be a critical endeavor for enhancing knowledge exchange, better evaluation of the practice, and more realistic understanding of the costs and benefits. Here, we describe how our multidisciplinary effort of co-producing knowledge informs understanding of the effectiveness of various fencing designs and more importantly provides a better mechanism for transferring this knowledge between producers, researchers, and land managers. We explain the process underway and demonstrate that incorporating producers and practitioners from the onset allows research priorities and expected outcomes to be set collaboratively, gives transparency to the agricultural community of the research process, provides a critical lens to evaluate efficacy and functionality, and will inform the practicality of fencing as a conflict prevention tool. We discuss opportunities and challenges of this co-production process and how it can be applied to other realms of fencing and conflict prevention strategies.